P112: In situ simulation: A team sport?. (May 2019) - Rusiecki, D.; Hoffe, S.; Walker, M.; Reid, J.; Rocca, N.; White, H.; McDonough, L.; Chaplin, T.
Abstract : Introduction : Identification of latent safety threats (LSTs) in the emergency department is an important aspect of quality improvement that can lead to improved patient care. In situ simulation (ISS) takes place in the real clinical environment and multidisciplinary teams can participate in diverse high acuity scenarios to identify LSTs. The purpose of this study is to examine the influence that the profession of the participant (i.e. physician, registered nurse, or respiratory therapist) has on the identification of LSTs during ISS.Methods : Six resuscitation- based adult and pediatric simulated scenarios were developed and delivered to multidisciplinary teams in the Kingston General Hospital ED. Each ISS session consisted of a 10- minute scenario, followed by 3-minutes of individual survey completion and a 7- minute group debrief led by ISS facilitators. An objective assessor recorded LSTs identified during each debrief. Surveys were completed prior to debrief to reduce response bias. Data was collected on participant demographics and perceived LSTs classified in the following categories: medication; equipment; resources and staffing; teamwork and communication; or other. Two reviewers evaluated survey responses and debrief notes to formulate a list of unique LSTs across scenarios and professions. The overall number and type of LSTs from surveys was identified and stratified by health care provider.Results : Thirteen ISS sessions were conducted with a total of 59 participants. Thirty- four unique LSTs (8 medication, 15 equipment, 5 resource, 4 communication, and 2 miscellaneous issues) were identified from surveys and debrief notes. Overall, MDs (n = 12) reported 19 LSTss (n = 41) reported 77 LSTs, and RTs (n = 6) reported 4 LSTs based on individual survey data. The most commonly identified category of LSTs reported by MDs (36.8%) and RTs (75%) was equipment issues while RNs most commonly identified medication issues (36.4%). Participants with □5 years of experience in their profession, on average identified more LSTs in surveys than participants with >5 years experience (1.9 LSTs vs 1.5 LSTs respectively).Conclusion : Nursing staff identified the highest number of LSTs across all categories. There was fairly unanimous identification of major LSTs across professions, however each profession did identify unique perspectives on LSTs in survey responses. ISS programs with the purpose of LST identification would benefit from multidisciplinary participation.